2006
DOI: 10.1111/j.1365-2559.2006.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous immunohistochemical expression of HBME‐1 and galectin‐3 differentiates papillary carcinomas from hyperfunctioning lesions of the thyroid

Abstract: An immunohistochemical panel consisting of HBME-1 and galectin-3 can make a correct distinction between malignant and hyperfunctioning thyroid neoplasms with high diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 19 publications
2
59
1
Order By: Relevance
“…A number of other molecules have been described later on as malignancy markers for thyroid carcinoma. Three of them, that is, HBME-1, galectine-3 (GAL3), and cytokeratine-19 (CK19), have been tried on cytological material and are considered useful (van Hoeven et al, 1998;Saggiorato et al, 2005;Rossi et al, 2006). However, almost all these studies were performed on cell blocks or thin-prep samples because of poor results on conventional smears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other molecules have been described later on as malignancy markers for thyroid carcinoma. Three of them, that is, HBME-1, galectine-3 (GAL3), and cytokeratine-19 (CK19), have been tried on cytological material and are considered useful (van Hoeven et al, 1998;Saggiorato et al, 2005;Rossi et al, 2006). However, almost all these studies were performed on cell blocks or thin-prep samples because of poor results on conventional smears.…”
Section: Discussionmentioning
confidence: 99%
“…The reported specificity of HBME-1 staining ranged from 70% to more than 90% (Cheung et al, 2001;Prasad et al, 2005;Saggiorato et al, 2005). Thyrotoxic hyperplasia was consistently negative (Rossi et al, 2006) whereas nodular goitres were positive in up to 17% of cases (Ito et al, 2005). Significant reactions were also reported in 25% of thyroiditis (Prasad et al, 2005), 5 -10% of benign follicular tumours devoid of atypical features, and up to 65% with LNFPTC or Hürthle cell features (Mai et al, 2002;Papotti et al, 2005;Prasad et al, 2005;Scognamiglio et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CK19 has been found to be strongly expressed in PTC in both cytologic and tissue specimens. 6,7,11,[15][16][17] In our study, 81% of FNABs from PTC and 93% of the corresponding histologic specimens showed strong and diffuse CK19 positivity. However, CK19 was strongly expressed in FNAB smears of 4 adenomas, 1 Hashimoto's thyroiditis and 1 nodular goiter and in histologic specimens of 1 adenoma, 1 Hashimoto's thyroiditis, 7 Hashimoto's thyroiditis concurrent with PTC and 1 nodular goiter.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,13 Moreover, this marker has been reported to be useful in cytologic smears and in cell block preparations for the diagnosis of PTC. [15][16][17] p53-Homologous nuclear protein p63 (p63) has been recently described for use in papillary thyroid carcinoma, [18][19][20][21][22] but to the best of our knowledge, p63 expression in FNAB of the thyroid has not been investigated before.…”
Section: Expression Of Cytokeratin 19 and Protein P63 In Fine Needle mentioning
confidence: 99%
“…10,11 Its utility in thyroid carcinomas has been documented in several studies, revealing strong and diffuse cytoplasmic staining in PTCs. [12][13][14][15][16][17] It is considered the most specific marker (96%) for PTC by some authors, and the most sensitive and specific marker by others, reportedly staining 96% of PTCs and only 7% of BTN cases. 12,13 Other studies have demonstrated that immunoreactivity for HBME-1 is an indication of thyroid malignancy, but not necessarily of papillary differentiation.…”
Section: Discussionmentioning
confidence: 99%